"I Am a Nice Person When I Do Yoga!!!": A Qualitative Analysis of How Yoga Affects Relationships. (June 2014) - Ross, Alyson; Bevans, Margaret; Friedmann, Erika; Williams, Laurie; Thomas, Sue
Purpose: To develop a better understanding of how yoga practice affects one's interpersonal relationships.Design: Qualitative.Method: Content analysis was used to qualitatively analyze written comments ( n = 171) made regarding yoga improving interpersonal relationships in a large cross-sectional survey of yoga practitioners ( N = 1, 067).Findings: Four themes were identified: Yoga practice leads to personal transformation, increases social interaction, provides coping mechanisms to weather relationship losses and difficulties, and leads to spiritual transcendence. Practitioners believed that their interpersonal relationships improved because their attitude and perspective had changed, making them more patient, kind, mindful, and self-aware. They expressed an aspect of community that was both practical (they met new friends) and spiritual (they felt they belonged). They thought they could better weather difficulties such as divorce and death. A number discussed feeling a sense of purpose and that their practice contributed to a greater good.Conclusions: There appears to be an aspect of community associated with yoga practice that may be beneficial to one's social and spiritual health. Yoga could be beneficial for populations at risk for social isolation, such as those who are elderly, bereaved, and depressed, as well as individuals undergoing interpersonal crises.